Environment and Regional Trade Agreements Developments in 2009 - Gallagher, Peter (OECD Publishing, 2010)
This document is a third update on developments in the field of regional trade agreements and environment covering the period late 2008 to December 2009. It complements the 2007 publication "Environment and Regional Trade Agreements" prepared under the aegis of the Joint Working Party on Trade and Environment. It is based on publicly available information and refers to agreements which have been signed by the Parties, though not all have entered into force yet
Keywords: Environment; Trade